The analysis of tropospheric aerosol concentration and distribution using NOAA AVHRR - Wan Kadir, Wan Hazli; Ibrahim, Ab. Latif; Rasib, Abdul Wahid; Mohd. Hassan, Aida Hayati; Zaini, Zawatil Azhani (Faculty of Geoinformation Science and Engineering, 2005)
The air quality indicator approximated by satellite measurements is known as atmospheric particulate loading, which is evaluated in terms of columnar optical thickness of aerosol scattering. The effect brought by particulate pollution has gained interest after recent evidence on health effects of small particles. This study presents the potentiality of using NOAA AVHRR data to obtain tropospheric aerosol distribution over Malaysian land area. Contrast reduction technique is used in order to extract the aerosol optical thickness (AOT). Differential textural analysis (DTA) algorithm is applied on the geometrically corrected images of NOAA AVHRR. The algorithm is applied onto three sequence years of NOAA AVHRR data. Correlation as high as 0.9567, 0.8633 and 0.8361 for respectively three sequence years, 2002, 2003 and 2004 are found between the retrieved AOT values and PM10 data. The results suggests that the application of DTA algorithm on NOAA AVHRR imagery whenever available and cloud free could be used as an indicator to air quality assessment for this region.